EFEKTIVITAS PENGELOLAHAN DESA EKOWISATA DIKECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN - LONDA, REYNOLD (Sam Ratulangi University, 2020)
the effectiveness of ecotourism is a measure of the achievements of the government and the sector concerned in the utilization of existing attractions that promote education, economic preservation of natural resources and the culture of the community, so that it can be said to prosper the community through the industrial sector which has the potential to be developed in the regional economy and the community ecotourism village. This research is a descriptive study with a qualitative approach. Data collection techniques in this study used the observation method of direct observation to the research location and conducting interviews and documentation. The purpose of this research is to describe the effectiveness of ecotourism village management in the district of south Minahasa regency. Based on the results of existing ecotourism management research in the district of Tatapaan that it has not been effective because the field findings indicate that the South Minahasa Regency Tourism Office has not paid attention to the management of the development of ecotourism villages and community empowerment. There is no program that encourages the implementation of policies in the management of ecotourism villages. No serious local government. improvement is needed in the preparation and implementation of tourism infrastructure development programs and seriousness in the management of ecotourism villagesÂ keywords: effectiveness, management, ecotourism, development